Web-based interventions for treatment-seeking individuals with hazardous alcohol consumption: analysis of clinical characteristics and motives for abstinence - Stüben, Nathalie; Muscheidt, Rosa; Kiefer, Falk; Soyka, Michael (Alcohol and alcoholism, 2025)
This study compared individuals with hazardous alcohol consumption who used the web-based intervention “Ohne Alkohol mit Nathalie” (OAMN) with individuals who relied exclusively on traditional support to enhance the understanding of OAMN user characteristics.A cross-sectional online survey included 2460 treatment-seeking participants with Alcohol Use Disorders Identification Test scores ≥8 indicating hazardous alcohol use. The OAMN group (n = 1825) included individuals who had used OAMN programs, while the non-OAMN group (n = 635) relied exclusively on traditional support. Analyses compared sociodemographic characteristics, psychiatric comorbidities, the extent to which OAMN was used as a standalone or complementary tool, alcohol consumption, and abstinence motives.Both groups were predominantly female and highly educated, but these characteristics were more pronounced among OAMN users. About one-third of OAMN users relied exclusively on the examined intervention, while two-thirds combined it with other forms of support. Non-OAMN users exhibited higher psychiatric comorbidities and had higher Alcohol Use Disorders Identification Test scores. Intrinsic motives were key drivers for abstinence in both groups, while these motives were more pronounced among OAMN users and extrinsic motives were more frequently reported by non-OAMN users.These findings show that OAMN primarily attracts well-educated women and that it’s used as both a standalone and complementary intervention. OAMN users were more likely to report intrinsic motives such as improving well-being and autonomy as key drivers for abstinence and less likely to report extrinsic motives such as external expectations and fear. These insights enhance understanding of the characteristics and abstinence motives of individuals engaging with OAMN.
Online veröffentlicht: 2. April 2025
Gesehen am 26.05.2025